Search for adaptive methods immunizing from high-noise, application on oil industry power complexes control telemetry model - Ustun, O.; Yilmaz, M.; Ali Zada, P.; Fedorchuk, V. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2012)
Here in the paper, an analog signal processing implementation was searched for the detection the most efficient adaptive noise cancellation filters among dozens of recognized ones for telemetry control systems of oil industry electrical submersible pump under severe noisily conditions. В предлагаемой статье для выполнения обработки аналогового сигнала погружаемых электрических насосов с высоким уровнем шумов был проведен поиск и найдены среди десятков известных наиболее эффективные адаптивные фильтры подавления помех для систем управления и телеметрии.